2011
DOI: 10.1016/j.chiabu.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Fatal child maltreatment in England, 2005–2009

Abstract: Fatal child maltreatment in England 2 Authors' ContributionsThe original idea for this paper came from Peter Sidebotham, who carried out the primary analysis and wrote the first and subsequent drafts of the paper.Sue Bailey and Pippa Belderson carried out the data extraction and coding and contributed to the analysis and to reviews of drafts of the paper.Marian Brandon had oversight of the main research project and contributed to data analysis and to reviews of drafts of the paper. Conflicts of InterestThe aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…As only children old enough for reading could answer, these questionnaires cannot help reduce deaths in the most vulnerable groups. Indeed, fatal child maltreatment occurs most frequently when children are younger [2,37-39]. Over a half of the 600 victims of child maltreatment under five years reported to the National Violent Death Reporting System of the United States of America from 2003 to 2006 were under one-year-old [40].…”
Section: Discussionmentioning
confidence: 99%
“…As only children old enough for reading could answer, these questionnaires cannot help reduce deaths in the most vulnerable groups. Indeed, fatal child maltreatment occurs most frequently when children are younger [2,37-39]. Over a half of the 600 victims of child maltreatment under five years reported to the National Violent Death Reporting System of the United States of America from 2003 to 2006 were under one-year-old [40].…”
Section: Discussionmentioning
confidence: 99%
“…5 Children in the first year of life are the most vulnerable to becoming victims of homicide, 6,7 including maternal infanticide. 8,9 The killing of female infants is a recognized problem in some patriarchal societies where girls are less valued than boys and viewed as a financial liability. 10 A homicide study in Dar-es-Salaam, in the United Republic of Tanzania, showed a very high rate of early infanticide (27.7 per 100 000 infants less than 1 week old) but an overall homicide rate among children younger than 15 years of 0.54 per 100 000.…”
Section: Introductionmentioning
confidence: 99%
“…England and Wales, where CDR is established under national Safeguarding Children legislation , appear to be an exception in Europe and may represent a good practice model that could feasibly be adopted in other countries.…”
Section: Discussionmentioning
confidence: 99%